Wintry night - Li, Qiao, 1934-; Li, Qiao, 1934- (New York : Columbia University Press, 2001)
An epic spanning more than half a century of Taiwan's history, this breathtaking historical novel traces the fortunes of the Pengs, a family of Hakka Chinese settlers, across three generations from the 1890s, just before Taiwan was ceded to Japan as a result of the Sino-Japanese war, through World War II. Li Qiao brilliantly re-creates the dramatic world of these pioneers?and the colonization of Taiwan itself?exploring their relationships with the aboriginal peoples of Taiwan and their struggle to establish their own ethnic and political identities. This carefully researched work o.
Part one. Wintry night -- Part two. The lone lamp.
Print version record.
In English.
JSTOR
Keywords: Li, Qiao, -- 1934- -- Translations into English; Li, Qiao, -- 1934-; LITERARY CRITICISM -- Asian -- General; FICTION -- Literary; Translations